Extracellular vesicles in neurodegenerative disease — pathogenesis to biomarkers - Thompson, A; Gray, E; Heman-Ackah, S; Mager, I; Talbot, K; El Andaloussi, S; Wood, M; Turner, M (Nature Publishing Group, 2016)
Reliable markers of diagnosis, disease activity and progression in neurodegenerative diseases are a research priority in the improvement of diagnosis and the development of effective disease-modifying therapies. The fact that neurodegenerative pathology is primarily associated with distinct subsets of cells in discrete areas of the CNS makes the identification of relevant biomarker molecules a challenge. The trafficking of macromolecules from the CNS to the cerebrospinal fluid and blood mediated by extracellular vesicles (EVs) presents a promising source of CNS-specific biomarkers. EVs are released by almost all cell types and carry a cargo of protein and nucleic acid that varies according to the cell of origin. EV output changes according to cell status and reflects intracellular events, so surface marker expression can be used to identify the cell type from which EVs originate. EVs could, therefore, provide an enriched pool of information about core neuropathogenic, cell-specific processes. This Review examines the current knowledge of the biology and function of EVs, discusses the evidence for their involvement in the pathogenesis of neurodegenerative diseases, and considers their potential as biomarkers of disease.